2013
DOI: 10.1130/g34318.1
|View full text |Cite
|
Sign up to set email alerts
|

Concordant monsoon-driven postglacial hydrological changes in peat and stalagmite records and their impacts on prehistoric cultures in central China

Abstract: Concordant monsoon-driven postglacial hydrological changes in peat and stalagmite records and their impacts on prehistoric cultures in central China Supplementary Materials Ages, hopanoid distribution and origin, archaeological sites, and the temperature record Table DR1. Results of 14 C AMS dating from Dajiuhu peatland profile, central China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
157
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 20 publications
8
157
1
1
Order By: Relevance
“…6. Comparison of selected representative Holocene humidity records from the EASM region: (A) paleoprecipitation record based on pollen assemblages from Gonghai Lake ; (B) hopanoid mass accumulation rates from Dajiuhu peat bog (Xie et al, 2013); (C) stalagmite ARM/SIRM record from Heshang Cave (Xie et al, 2013); (D) ΔδC 31-29 record from Huguangyan Lake (Jia et al, 2015); and west-east Equatorial Pacific thermal gradient record (E, Koutavas and Joanides, 2012) and Northern Hemisphere summer insolation record (F, Laskar et al, 2004Laskar et al, , 2011. The blue bars represent the humid interval of the mid-Holocene (ca.…”
Section: Evolution Of Humidity In the Easm Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…6. Comparison of selected representative Holocene humidity records from the EASM region: (A) paleoprecipitation record based on pollen assemblages from Gonghai Lake ; (B) hopanoid mass accumulation rates from Dajiuhu peat bog (Xie et al, 2013); (C) stalagmite ARM/SIRM record from Heshang Cave (Xie et al, 2013); (D) ΔδC 31-29 record from Huguangyan Lake (Jia et al, 2015); and west-east Equatorial Pacific thermal gradient record (E, Koutavas and Joanides, 2012) and Northern Hemisphere summer insolation record (F, Laskar et al, 2004Laskar et al, , 2011. The blue bars represent the humid interval of the mid-Holocene (ca.…”
Section: Evolution Of Humidity In the Easm Regionmentioning
confidence: 99%
“…We selected results from the Dajiuhu peat bog and stalagmite from Heshang Cave (Fig. 1), from the middle reaches of the Yangtze River, to represent the Holocene paleo-humidity evolution of the area (Xie et al, 2013). The mass accumulation rates of hopanoids from Dajiuhu peat bog were adopted as indicators of water level variations in the peatland.…”
Section: Evolution Of Humidity In the Easm Regionmentioning
confidence: 99%
“…Speleothems may grow continuously for thousands of years, and can be dated with very high accuracy and precision using 230 Th dating, a technique that can be reliably used on specimens younger than 700-600 ka (Edwards et al, 2003;Dorale et al, 2004;Cheng et al, 2013). Recent speleothem magnetism studies have shown that magnetic minerals encapsulated in stalagmites (e.g., Strauss et al, 2013;Font et al, 2014) can be used successfully in dating geomagnetic excursions (Osete et al, 2012), as well as for reconstructing hydrologic and climatic variations (Xie et al, 2013;Bourne et al, 2015). Here we present a speleothem geomagnetic record from Crevice Cave, Missouri, USA (Dorale et al, 1998) that captures the changes in geomagnetic field direction and intensity associated with the Laschamp excursion, dated directly on speleothem calcite using a combination of high-precision 230 Th dating and incremental chronometry from annual growth laminae.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in measurement sensitivity have opened up speleothems as viable archives of magnetic information (7,11). Here, we examine whether such magnetic records can provide an opportunity to identify extreme precipitation events, such as storms, by measurement of magnetic minerals in a stalagmite from central China, a region strongly influenced by both the Eastern Asian and Indian monsoon systems.…”
mentioning
confidence: 99%
“…Magnetic minerals, transported by groundwater from soils overlying the cave system, are incorporated into speleothems as they grow, and long-term changes in precipitation can be recorded by magnetic minerals in speleothems (7)(8)(9)(10)(11). Recent advances in measurement sensitivity have opened up speleothems as viable archives of magnetic information (7,11).…”
mentioning
confidence: 99%